Use of Morpho-physiological Parameters and Biochemical Markers to Select Drought Tolerant Genotypes of Durum wheat - El Keroumi, Ismail Outoukarte, Abderrahim; Dihazi, Abdelhi; Naamani, Khalid (Journal of Plant Stress Physiology)
Nine durum wheat genotypes (Karim, Ourghi, Massa, Isly, Vitron, Sebou, Oum Rbia, Sarif, and Marzak) were grown in pots and evaluated for their phenolic content and peroxidases activity (POX), cell membrane stability (CMS) and Stomatal Resistance (SR). The genotypes Ourghi and Karim exhibited the highest amount of total phenolics (1374 µg.g-1 FW and 1303 µg.g-1 FW respectively) while Massa and Oum Rbia showed the lowest amounts (676 µg.g-1 FW and 761 µg.g-1 FW respectively) under severe stress regime. High performances Liquid Chromatography (HPLC) analysis revealed an important accumulation of hydroxycinnamic acid derivatives for the most accumulating genotypes. Under severe drought stress conditions, Ourghi revealed the highest peroxidase activity and Oum Rbia the lowest. A positive correlation was obtained between total phenolics and CMS. In another experiment hold in the hydroponic system under normal growing conditions, we revealed the superiority of genotype Karim in term of tillers, leaves and roots number, root thickness and dry matter accumulation and allocation to the roots. The present data provide useful information about whether the parameters used in this study are helpful in understanding drought tolerance mechanisms and the possibility to use them in selection programs under Mediterranean conditions.